Factors Influencing Young Voters' Political Participation in the 2020 Regional Elections in Yogyakarta - Budhyatma, Erlangga Hikmah; Pribadi, Ulung (Universitas Pendidikan Ganesha, 2024)
In the midst of the pandemic, which caused a profound crisis for the people, the government continued to hold the 2020 simultaneous Regional Head Elections (PILKADA). This decision faced opposition from the public, with surveys conducted by research institutions showing that much of the opposition was dominated by the youth demographic. The purpose of this study is to explore the factors influencing political participation among young voters in the 2020 Regional Head Elections in the Special Region of Yogyakarta (DIY). This research uses a quantitative approach, with data collected through a questionnaire distributed via Google Forms, gathering responses from 50 participants. Data analysis was carried out using SmartPLS software. This study employs the EUCS (End User Computing Satisfaction) model to examine the factors that influence political participation among young voters in the 2020 PILKADA in DIY, focusing on several variables: Attitude, Work Experience, Track Record, and Education Level. The results, based on the R-Square value, show that the factors influencing young voters' political participation in the 2020 simultaneous Regional Head Elections in DIY namely Attitude (S), Work Experience (PK), Track Record (RJ), and Education Level (TP) account for 0,960. Therefore, it can be concluded that the political participation of young voters in the 2020 simultaneous Regional Head Elections in DIY is influenced by these factors to an extent of 96.0%.